Partial Intestinal Obstruction Caused by Left Diaphragmatic Hernia: A Case Report - Pirade, Audi; Paat, Rigel K.; Tangkilisan, Adrian (e-CliniC, 2026)
Abstract: Diaphragmatic hernia in adults is a rare but potentially serious condition that often presents with non-specific gastrointestinal and respiratory symptoms. This case highlights a left-sided diaphragmatic hernia complicated by partial intestinal obstruction. We reported a 54-year-old male presented with a one-week history of progressive abdominal bloating and intermittent abdominal pain, accompanied by nausea but no vomiting or fever. Bowel movements and flatus were present. In examination, he was hemodynamically stable with abdominal distension and positive bowel sounds. Nasogastric tube drainage produced greenish fluid. Digital rectal examination showed normal stool without blood or mucus. Chest X-ray suggested a left diaphragmatic hernia, and abdominal X-ray revealed partial bowel obstruction without signs of pneumoperitoneum. Laboratory findings were within normal limits, except for mild hypokalemia (K⁺ 3.3 mmol/L). A diagnosis of partial mechanical intestinal obstruction due to a left diaphragmatic hernia was made. The patient underwent an urgent non-contrast abdominal CT followed by combined laparotomy and thoracotomy. Intraoperatively, a diaphragmatic defect (3×3 cm and 10×10 cm) with adhesions between the left lung and diaphragm was identified. Adhesiolysis was performed, and the defect was repaired using non-absorbable sutures, followed by diaphragmatic plication and chest tube insertion. In conclusion, this case underscores the importance of including diaphragmatic hernia in the differential diagnosis of adult patients with persistent abdominal symptoms. Timely imaging and a multidisciplinary surgical approach enabled resolution of obstruction and definitive repair, preventing serious complications. In conclusion, early recognition and appropriate surgical management are key to optimizing outcomes in adult diaphragmatic hernia with bowel involvement. Keywords: diaphragmatic hernia; intestinal obstruction